Kritik Terhadap Muhammad Abduh Tentang Perkawinan Antar Muslim dengan Ahl Kitab dan Musyrik - Dawam, Fahrul (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2023)
Other religious marriages are marriage bonds that occur between people who do not share the same beliefs. Between followers of the Islamic religion, whether a Muslim or Muslim woman, with followers of religions other than Islam, including those who are polytheists or believers of the Bible. Due to differences in interpretation in the Koran which forbids marriage between Muslims and those with the status of polytheists or people of the Bible, the issue of interfaith marriage often becomes a controversy among ulama, and what is most prominent is the subject of debate in this case according to the author. is about the concept of ma’na musyrik and ahl al-kitab in the view of Muhammad Abduh. According to Muhammad Abduh, the marriage laws among Muslims and Ahlul kitab as well as polytheists are as follows: A Muslim man marries a polytheist woman. 1)The marriage of a Muslim woman between a Muslim man. 2) Marriage of a Muslim man between an Ahl al-Kitab woman. The author criticizes Muhammad Abduh’s ijtihad, which states that the law on marriage between Muslims and people of the book is absolutely permissible. In this case, the author is of the view that this tends to be very risky in the aqidah and believes that marriage between Muslim men and women from people of the book should be avoided for the purposes of lisaddil dhari’ah. Keywords: Ahl Al-Kitab, Mushrik, Marriage